Gender creativity versus sex-gender system: Voices of trans* children and adolescents - Elena María Gallardo Nieto; María Espinosa Spínola (Revista Sobre la Infancia y la Adolescencia)
This paper reflects on the way in which gender is built in our society and how such construction is internalized and/or answered by gender creative children. In this sense, we consider that transgressing a rigid binary sex-gender system and not responding to the established sociocultural mandates entails for these subjects to experience forms of violence(s) that fall on their bodies. The purpose of the research that is presented is, on the one hand, to know the way in which gender creative children respond to the sex-gender system from their subjectivity and, on the other hand, to show the expressions of violence(s) that they experience by not responding to cis-gender assignment at birth. Our methodological approach to this reality is based on five case studies, using qualitative research techniques such as interviews and readings. The research had lasted two years, beginning on the 2015 and finishing on the 2017. The research subjects have been five trans* children between nine and sex-teen years old located in Andalusia, Spain.